1969
DOI: 10.1126/science.164.3879.580
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Saluretic Activity: Its Nature and Relation to Oxytocin Analogs

Abstract: Plasma natriuretic activity was evoked in cows and dogs by infusion of saline with or without dextran. Deproteinized samples were fractionated on both Sephadex and Bio-Gel columns; the activity was separated, the approximate molecular weight being in the region of 1000. Incubation with chymotrypsin destroyed the activity, suggesting that it might be a polypeptide. A similar activity in blood resulted from intracarotid injection of either oxytocin or either of two synthetic analogs. Possibly the latter are salu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Unconvincing evidence for a natriuretic hormone has also been advanced by Cort (8), Cort (32), and Sedlakova, Lichardus, and Cort (33). Their terial described herein because it is dialyzable and has a substance produces very unimpressive increases in so-molecular weight said to be from 800 to 1000.…”
Section: Discussionmentioning
confidence: 89%
“…Unconvincing evidence for a natriuretic hormone has also been advanced by Cort (8), Cort (32), and Sedlakova, Lichardus, and Cort (33). Their terial described herein because it is dialyzable and has a substance produces very unimpressive increases in so-molecular weight said to be from 800 to 1000.…”
Section: Discussionmentioning
confidence: 89%
“…After the infusion of the control fraction, there was no significant change in any of the parameters. Immediately after infusion of the expanded fraction IV there was an increase in V from 10 and in FENa from 1.29 to 5.22%; GFR remained constant. The increase in UN.V persisted for 120 min before returning to base-line values.…”
Section: Resultsmentioning
confidence: 96%
“…Finally, and most critically, the presence of the inhibitor in the urine of patients and dogs with chronic uremia and of the present dogs with normal renal function appears to correlate with the dictates of maintaining external sodium balance. A number of other investigators have now demonstrated the presence of natriuretic factor(s) or inhibitor(s) of sodium transport in the blood of animals and man using whole animal experiments (13)(14)(15)(16)(17)(18)(19)(20)(21) or in vitro assays (13,18,20,(22)(23)(24)(25)(26)(27)(28)(29). Similarly, extracts of urine have also been shown to contain natriuretic substance(s) (16,17,19,20,(30)(31)(32)(33)(34)(35)(36) or inhibitor(s) of sodium transport (20,37,38).…”
Section: Discussionmentioning
confidence: 99%